Correlations Between Body Weight and Size-Specific Dose Estimate on Thoracic Computed Tomography Examination - A. L. Wati; C. Anam; A. Nitasari; S Syarifudin; G. Dougherty (PPIKSN-BATAN, 2022)
The dose received by a patient on CT examination is expressed in size-specific dose estimates (SSDE) which is a function of the patient diameter, x-ray attenuation, and scanner output (volume computed tomography dose index, CTDIvol). Patient diameter and x-ray attenuation are represented as water equivalent diameter (Dw). We conducted the research to analyze the relationships between body weight and Dw, CTDIvol, and size-specific dose estimates (SSDE) in contrast-enhanced thorax examinations. We used images from 100 patients (50 women and 50 men patients) whose weight range from 2.8 kg to 80 kg. The values of Dw, CTDIvol, and SSDE were automatically calculated from axial CT images using the IndoseCT software. Statistical analysis showed that the patient's body weight correlates linearly with the Dw. The linearity coefficient (R2) values for body weight and Dw is 0.43 (women) and 0.55 (men). However, weight was independent of the patient dose in terms of CTDIvol and SSDE. This was because the CT system used tube current modulation (TCM), which automatically adapted the tube current to patient size, resulting in a relatively constant dose regardless of the patient size (Dw).